Muftis of European Russia and Siberia in the late XVIII-early XXI centuries - Rail Ravilovich Fahrutdinov, Aidar Yurievich Khabutdinov, Marina Maratovna Imasheva,; Aidar Nilovich Youzeev, Mariam Rifgatevna Yafyasova, (Opción, 2019)
The purpose of the article is to understand the mechanisms of the formation of the Muslim elite at the level of the Mufti Institute in the conditions of the growing importance of the Islamic factor in Russia via the methods of institutional analysis, problem and comparative history. As a result, the Russian Muftis both in the Imperial and in the modern period sought not only to secure this position for a lifetime, but also to transfer it by inheritance. In conclusion, in the post-Soviet period, we see that the post of Mufti can again provide economic capital.